Understanding Parents’ Roles in Children’s Learning and Engagement in Informal Science Learning Sites - Joy, Angelina; Law, Fidelia; McGuire, Luke; Mathews, Channing; Hartstone-Rose, Adam; Winterbottom, Mark; Rutland, Adam; Fields, Grace E.; Mulvey, Kelly Lynn (Frontiers in Psychology, 2021)
Informal science learning sites create opportunities for children to learn about science outside of the classroom. This study analyzed children’s learning behaviors in informal science learning sites using video recordings of family visits to a zoo, children’s museum, or aquarium. Furthermore, parent behaviors, features of the exhibits and the presence of an educator were also examined in relation to children’s behaviors. Participants included 63 children (60.3% female) and 44 parents in 31 family groups. Results showed that parents’ science questions and explanations were positively related to children observing the exhibit. Parents’ science explanations were also negatively related to children’s science explanations. Furthermore, children were more likely to provide science explanations when the exhibit was not interactive. Lastly there were no differences in children’s behaviors based on whether an educator was present at the exhibit. This study provides further evidence that children’s interactions with others and their environment are important for children’s learning behaviors.